Multi-stage nozzle-shape optimization for pulsed hydrogen–air detonation combustor. (February 2017) - Ornano, Francesco; Braun, James; Saracoglu, Bayindir Huseyin; Paniagua, Guillermo
Thermal engines based on pressure gain combustion offer new opportunities to generate thrust with enhanced efficiency and relatively simple machinery. The sudden expansion of detonation products from a single-opening tube yields thrust, although this is suboptimal. In this article, we present the complete design optimization strategy for nozzles exposed to detonation pulses, combining unsteady Reynolds-averaged Navier–Stokes solvers with the accurate modeling of the combustion process. The parameterized shape of the nozzle is optimized using a differential evolution algorithm to maximize the force at the nozzle exhaust. The design of experiments begins with a first optimization considering steady-flow conditions, subsequently followed by a refined optimization for transient supersonic flow pulse. Finally, the optimized nozzle performance is assessed in three dimensions with unsteady Reynolds-averaged Navier–Stokes capturing the deflagration-to-detonation transition of a stoichiometric, premixed hydrogen–air mixture. The optimized nozzle can deliver 80% more thrust than a standard detonation tube and about 2% more than the optimized results assuming steady-flow operation. This study proposes a new multi-fidelity approach to optimize the design of nozzles exposed to transient operation, instead of the traditional methods proposed for steady-flow operation.